2006
DOI: 10.1001/jama.296.4.397
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Patients at Low Risk for Recurrent Venous Thromboembolism by Measuring Thrombin Generation

Abstract: Measurement of thrombin generation identifies patients at low risk for recurrent VTE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
227
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(244 citation statements)
references
References 23 publications
13
227
1
1
Order By: Relevance
“…Although studies have demonstrated significant correlations between TGA parameters and both hemostatic defects [22] and primary and recurrent thrombosis [9, 23–25], the assay has not yet received regulatory approval for clinical use from either the U.S. Food and Drug Administration or European Medicines Agency, in part due to difficulties with assay standardization. In particular, thrombin generation measurements are highly sensitive to pre-analytical variables, including the method of blood collection and plasma isolation (tube style, presence or absence of contact pathway inhibitors, centrifugation speeds and freezing methods), and analytical variables (tissue factor level, lipid concentration, use or not of calibrators) [26].…”
Section: Thrombin Generation Assaysmentioning
confidence: 99%
“…Although studies have demonstrated significant correlations between TGA parameters and both hemostatic defects [22] and primary and recurrent thrombosis [9, 23–25], the assay has not yet received regulatory approval for clinical use from either the U.S. Food and Drug Administration or European Medicines Agency, in part due to difficulties with assay standardization. In particular, thrombin generation measurements are highly sensitive to pre-analytical variables, including the method of blood collection and plasma isolation (tube style, presence or absence of contact pathway inhibitors, centrifugation speeds and freezing methods), and analytical variables (tissue factor level, lipid concentration, use or not of calibrators) [26].…”
Section: Thrombin Generation Assaysmentioning
confidence: 99%
“…Chromogenic assays require the utilization of defibrinated plasma samples in the analysis due to increased interference from the resulting turbidity when fibrinogen is added to the assay. Fluorogenic assays are more sensitive allowing for the use of smaller sample sizes compared to their chromogenic counterparts, however, there is no direct linear correlation between the fluorescence signal and thrombin activity [28].…”
Section: Introductionmentioning
confidence: 99%
“…Such a role ascribed to thrombin has been examined, with elevated endogenous thrombin potential (ETP) and peak thrombin levels demonstrated in venous thromboembolism and acute coronary artery disease and speculated in ischaemic stroke [12, 1517]. There is increasing speculation about dissimilar trend in thrombin generation kinetics in VTE which showed elevated ETP and PTG, when compared to coronary artery disease with elevated lag time and time to peak [15, 1820]. Such discordant trend has been suggested in stroke of different aetiological types [16, 21].…”
Section: Introductionmentioning
confidence: 99%